Editorial policies on election news : a study of the pre-1978 general election news in the New Straits Times and the Utusan Ma - Ngooi, Ning Ching (Universiti Sains Malaysia, 1982)
information is essential to us.We need information for decision making day to day.The press,whose function is to put the information regardless of party affilliation or self interest.